MODEL OF COMPETENCY DEVELOPMENT IN THE PERSONALITY OF ENGLISH TEACHER CANDIDATES THROUGH STUDENT DEVELOPMENT MANAGEMENT BASED ON ISLAMIC ACADEMIC CULTURE - Nuridin Nuridin; Choiril Anwar (JOALL (Journal of Applied Linguistics and Literature), 2019)
The English Language Education Study Program of Sultan Agung Islamic University (Unissula) has formulated a vision to become a leading study program in building the generation of khaira ummah, developing science and technology on the basis of Islamic values, and building Islamic civilization towards a prosperous society blessed by Allah. The effort to realize this vision was carried out through the implementation of Islamic Academic Culture as an implementation of fostering students who gave birth to the best generation. This study aims to (1) find a student development management model based on Islamic Academic Culture at Sultan Agung Islamic University, (2) find a model of personality development competence in English Education Study Program students as prospective teachers. This research was conducted at Sultan Agung Islamic University. The study population was students of the English Language Study Program, Dean and Deputy Dean of Academic and Student Affairs. Data were collected through interviews, questionnaires and documentation. Data then were analyzed by descriptive analysis. The results of the study show that (1) The factual model that has been carried out by Unissula in student development is based on three guidelines in its management, namely Unissula's vision, Unissula's Strategic Plan (Renstra), and Islamic Academic Culture values. The student development program is generally carried out through three stages, namely the initial stage when new students enter, coaching is done through the Pekan Taaruf program, the second stage, when becoming a student, guidance is carried out through tutorials, reasoning, leadership, entrepreneurship, and interest-sharing programs. talent. In the third stage of training before graduation students, it is conducted through a debriefing program; (2) the model of Islamic Academic Culture-based student development is effectively used in an effort to improve the personal competence of English Education Study Program students.